Análisis Cuantitativo: "Comportamiento de la Rentabilidad de los Depósitos en el Sistema Bancario Peruano 2008 - 2011 - Zavaleta López, María Cecilia (2012)
The present research has studied economic and financial variables considered by economic agents in their financial decisions, in the specific case of families with respect to the rates of return of their savings in the banking system of our country, in order to contribute To be more efficient and effective the process of financial decision-making and investment of families. The research has been developed based on information provided by statistical reports of the Central Reserve Bank of Peru, the National Institute of Statistics and Information Technology and the Superintendency of Banking and Insurance. The procedure followed in the investigation was first to compile and process the information of the exchange rate, inflation and of the average passive effective interest rate of the banking system, as well as of the different types of deposits; The rate of return of the family savings in nominal and real values, in both national and foreign currency, was then determined. Finally, we identified the trend that have followed the rates of return of deposits in the banking system. It is concluded that the real rate of return of the different types of deposits are negative both in national currency and in foreign currency, with the exception of time deposits of 360 days in national currency, with decreasing trend, this being one of The reasons why there are no incentives to improve the level of domestic savings in the country.